Management strategies of non-profit community sport facilities in an era of austerity. Issue 3 (27th May 2019) - Parnell, Daniel; May, Anthony; Widdop, Paul; Cope, Ed; Bailey, Richard
ABSTRACT: Research Question: This qualitative research explores the impact of austerity on community sport facilities across England (United Kingdom), drawing upon resource dependence theory (RDT) embedded within network theory. Research Methods: In-depth semi-structured interview data were collected from 24 stakeholders related to community sport facilities ( n = 12 facility managers, n = 6 regional grant managers, n = 6 national funders both third sector and corporate). The qualitative data were thematically analysed to understand the impact of austerity on how community sport facilities managed their organisations and operations. Results and Findings: The findings from this research offer insight into the challenges that community sport facilities are encountering which have resulted from austerity, and a shrinking of the funding from the central Government to local public services. Furthermore, different community sport facilities have navigated these challenges to maintain sustainability, essentially through adapting network structure and through income dynamism. In addition, using a network theory approach alongside RDT within a sporting context has allowed us to address issues on how network flow and structure impact sustainability and operations within and between organisations. Implications: The article offers managerial recommendations for community sport facility managers, practitioners and policy makers who operate in times of fiscal constraint. It recommends that future sport research utilises and applies both RDT and network theory to examine these changes and the subsequent management strategies adopted to overcome the associated challenges of fiscal constraint.